Factors associated with parental hesitancy towards the human papillomavirus vaccine: a cross-sectional study - Monela Mah-Ngum Ntonifor; Nkengeh Ntangatung Tazinkeng; Ben-Lawrence Kemah; Noumbissie Evenge Claudia; Yonta Kenne Sonia; Sangwe Clovis Nchinjoh; Clarence Mvalo Mbanga; Marwa Maweya Abdelbagi Elbasheer; Valirie Ndip Agbor (Scientific Reports)
Abstract Cervical cancer is the second most common cancer among females in Cameroon, with human papillomavirus (HPV) being the primary cause. While HPV vaccines are highly effective and have been introduced by Cameroon’s Ministry of Health (MOH), uncertainties persist regarding the determinants of HPV-related vaccine hesitancy. This study investigated the factors associated with parental HPV and cervical cancer awareness as well as parental HPV vaccine hesitancy in Cameroon. This cross-sectional study included 1,187 participants residing in Buea Health District (BHD) from August 2023 to March 2024. A pretested questionnaire adapted from the WHO’s vaccine hesitancy tool was used for data collection. Multivariable logistic regression generated adjusted odds ratios for lack of awareness and vaccine hesitancy. Younger ages and lower education levels were significantly associated with greater odds of HPV and cervical cancer unawareness. Parents with lower educational attainment and those unaware of HPV and cervical cancer had higher odds of vaccine hesitancy. Additionally, concerns about vaccine safety and side effects, distrust in the MOH and pharmaceutical companies, and lack of support from religious leaders were associated with parental vaccine hesitancy. In contrast, parents with a history of chronic illness had lower odds of being hesitant. The study identified several factors associated with parental HPV vaccine hesitancy. Addressing these factors could play a key role in improving vaccine uptake among children and eventually reducing cervical cancer rates in Cameroon.